A study on nomophobia and its correlation with sleeping difficulty and anxiety among medical students in a medical college, Telangana - Veerapu, Nagapraveen; Baer Philip, Ravi Kumar; Vasireddy, Hanisha; Gurrala, Sowmya; Kanna, Swathi Tapaswi (International Journal Of Community Medicine And Public Health, 2019)
Background: Social media and digital communication have become a part of life. Many things were made easy through online connectivity. The mobile phones not only connects people at anytime, anywhere and with anybody, but also movable and portable. Mobile phones when used extensively may cause a number of physical and psychological problems. Nomophobia (NO-MObile phone-PHOBIA) is one of the psychological problems related to exclusive use of mobile phone. It is the fear/anxiety of being away from mobile phone contact. The objectives are to study grading of nomophobia and to find out any correlation exits between nomophobia and sleeping difficulty and anxiety among medical students. Methods: A cross sectional study is conducted for duration of 6 months among medical students using semi-structured questionnaire. Nomophobia questionnaire (NMP-Q) is used to assess nomophobia, Athens insomnia scale is used to assess sleeping difficulty and general anxiety disorder- 7 Item scale is used to assess general anxiety. Results: The study showed that out of 364 students, 62 (17%) have mild, 234 (64.3%) have moderate and 68 (18.7%) have severe nomophobia. There is a weak positive correlation between nomophobia and sleeping difficult and anxiety. Conclusions: There problem of nomophobia is alarming; there is a need to reduce nomophobia, and to evolve effective strategies to enhance human interaction.